Resistance and endurance exercise training improves muscle mass and the inflammatory/fibrotic transcriptome in a rhabdomyosarcoma model. Issue 2 (16th February 2023) - Collao, Nicolas; Sanders, Olivia; Caminiti, Taylor; Messeiller, Laura; De Lisio, Michael
Abstract: Background: Rhabdomyosarcoma (RMS) is an aggressive soft tissue sarcoma that most often develops in children. Chemoradiation therapy is a standard treatment modality; however, the detrimental long‐term skeletal muscle consequences of this therapy in juvenile cancer survivors include muscle atrophy and fibrosis resulting in decreased physical performance. Using a novel model of murine resistance and endurance exercise training, we investigate its role in preventing the long‐term effects of juvenile RMS plus therapy. Methods: Four‐week‐old male ( n = 10) and female ( n = 10) C57Bl/6J mice were injected with M3‐9‐M RMS cell into the left gastrocnemius with the right limb serving as an internal control (CON). Mice received a systemic vincristine injection and then five doses of 4.8 Gy of gamma radiation localized to the left hindlimb (RMS + Tx). Mice were then randomly divided into either sedentary (SED) or resistance and endurance exercise training (RET) groups. Changes in exercise performance, body composition, myocellular adaptations and the inflammatory/fibrotic transcriptome were assessed. Results: RET improved endurance performance ( P < 0.0001) and body composition ( P = 0.0004) compared to SED. RMS + Tx resulted in significantly lower muscle weight ( P = 0.015) and significantly smaller myofibre cross‐sectional area (CSA) ( P = 0.014). Conversely, RET resulted in significantly higher muscle weight ( P = 0.030) and significantly larger Type IIA ( P = 0.014) and IIB ( P = 0.015) fibre CSA. RMS + Tx resulted in significantly more muscle fibrosis ( P = 0.028), which was not prevented by RET. RMS + Tx resulted in significantly fewer mononuclear cells ( P < 0.05) and muscle satellite (stem) cells (MuSCs) ( P < 0.05) and significantly more immune cells ( P < 0.05) than CON. RET resulted in significantly more fibro‐adipogenic progenitors ( P < 0.05), a trend for more MuSCs ( P = 0.076) than SED and significantly more endothelial cells specifically in the RMS + Tx limb. Transcriptomic changes revealed significantly higher expression of inflammatory and fibrotic genes in RMS + Tx, which was prevented by RET. In the RMS + Tx model, RET also significantly altered expression of genes involved in extracellular matrix turnover. Conclusions: Our study suggests that RET preserves muscle mass and performance in a model of juvenile RMS survivorship while partially restoring cellular dynamics and the inflammatory and fibrotic transcriptome.